Decree-Law of the Arab Republic of Egypt No. 141 of the 2014 Organizing the Activity of Microfinance = قرار رئيس جمهورية مصر العربية بالقانون رقم 141 لسنة 2014 بتنظيم نشاط التمويل متناهي الصغر / presidency - Egypt. presidency (2025)
Decree-law of the president of the Arab republic of Egypt no. 141 of the year 2014 organizing the activity of microfinance قرار رئيس جمهورية مصر العربية بالقانون رقم 141 لسنة 2014 بتنظيم نشاط التمويل متناهى الصغر